Earning on Response Coefficient in Automobile and Go Public Companies - Lisdawati Arifin (Universitas Islam Negeri Raden Mas Said Surakarta, 2017)
This study aims to analyze factors that influence earnings response coefficients (ERC), simultaneously and partially, composed of leverage, the systematic risk (beta), growth opportunities (market to book value ratio), and the size of the firm (firm size), selection of the sample in this study the author take 12 automakers and components that meet the criteria of completeness of the data from the year 2008 to 2012, entirely based on consideration of the following criteria: (1) the company's automotive and components are listed on the stock exchange, (2) have the financial statements years 2008-2012 (3) has a return data (closing price) the first day after the date of issuance of the financial statements. This study uses secondary data applying multiple linear regression models to analyze and test the effect of independent variables on the dependent variable partially (t-test), simultaneous (f-test), and the goodness of fit (R-square) on a research model. The result shows that leverage, beta, growth opportunities (market to book value ratio) and size along with (simultaneously) the effect on the dependent variable (dependent variable) earnings response coefficients. Partially leverage negatively affect earnings response coefficients, partially beta negatively correlated earnings response coefficients, partially growth opportunities (market to book value ratio) significant effect on earnings response coefficients, partially sized companies (firm size) significantly influenceÂ earnings response coefficients.Keywords: earnings response coefficients, leverage, systematic risk (beta) Growth opportunities, size of the companyÂ